Preparation method of high-ionic-conductivity solid electrolyte material of solid-state battery
By performing solvent-free dry mixing and heat treatment under an inert atmosphere, combined with the use of solid and gas purification agents, the problem of miscellaneous phases in the preparation of sulfide solid electrolytes is solved, and the purity of the electrolyte and battery performance are improved.
Patent Information
- Application Number
- CN202411574258.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-03-21
AI Technical Summary
Miscellaneous phases are easily introduced during the preparation of sulfide solid electrolytes, resulting in a decrease in electrochemical performance and affecting the energy density and rate performance of all-solid-state batteries.
The mixed raw materials and solid purification agent are mixed and heat-treated under an inert atmosphere by solvent-free and dry methods. By introducing solid purification agents and/or gas purification agents, the generation of heterogeneous phases is effectively reduced.
It improves the purity and ionic conductivity of sulfide solid electrolytes, enhances electrochemical stability, improves the rate performance and energy density of all-solid state batteries, and provides a solid material foundation for the commercial application of batteries.
Smart Images

Figure CN119660688A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a method for preparing a solid electrolyte material with high ionic conductivity for solid-state batteries. Background Art
[0002] In the development of modern energy storage technology, all-solid-state lithium batteries have become a hot topic of research due to their excellent safety and energy density. Solid electrolytes are an indispensable component of all-solid-state batteries and play a vital role in the performance of batteries. Among them, sulfide solid electrolytes have been considered the most promising. Sulfide solid electrolytes not only exhibit high ionic conductivity at room temperature, but also have good mechanical properties and are easy to process. These characteristics make sulfide solid electrolytes have broad application prospects in all-solid-state batteries.
[0003] Although sulfide solid electrolytes have performed well in laboratory-scale research, they still face a series of challenges in actual industrial production and application. One of the main problems is that impurities are easily introduced during the preparation of sulfide electrolytes. These impurities may come from a variety of factors, including the raw material Li2S easily reacting with water and oxygen to form LiOH or Li2O, and the high vapor pressure of sulfur-containing raw materials during the sintering process leading to the volatilization of phosphorus pentasulfide gas. The generation of these impurities will lead to a decrease in the electrochemical performance of sulfide solid electrolytes, ultimately affecting the energy density and rate performance of the battery, hindering the commercial application of sulfide electrolytes in all-solid-state batteries. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a method for preparing a solid electrolyte material with high ionic conductivity for solid-state batteries, which can reduce the generation of impurities, improve the purity and ionic conductivity of sulfide solid electrolytes, and provide a solid material foundation for improving the performance and reliability of all-solid-state batteries.
[0005] The technical solution adopted by the present invention to solve the above technical problems is: a method for preparing a solid electrolyte material with high ionic conductivity for a solid-state battery, comprising the following steps:
[0006] S1. Under the protection of an inert atmosphere, the mixed raw material and the solid purifying agent are mixed to obtain a powder after uniform mixing;
[0007] S2, heat treating the powder;
[0008] S3. After cooling, a sulfide solid electrolyte is obtained.
[0009] Preferably, in step S1, the solid purifying agent is a pure sulfur element or a mixture whose main phase is sulfur element or one or a combination of at least two of sublimated sulfur, amorphous sulfur, refined sulfur, P2S5, P4S3, and the content of the solid purifying agent is 0.5-1.5wt%.
[0010] Preferably, in step S2, a gas purifying agent is introduced while the powder is being heat treated.
[0011] And a method for preparing a solid electrolyte material with high ionic conductivity for a solid-state battery, comprising the following steps:
[0012] S1. Under the protection of an inert atmosphere, the mixed raw materials are mixed to obtain a powder after uniform mixing;
[0013] S2, introducing a gas purifying agent and heat treating the powder;
[0014] S3. After cooling, a sulfide solid electrolyte is obtained.
[0015] Preferably, in step S2, the gas purifying agent is one or a combination of H2S and S2, and the flow rate of the gas purifying agent is 0.5-3 mL / s.
[0016] Preferably, in step S1, the mixed raw material includes lithium sulfide and phosphorus sulfide; or, the mixed raw material includes lithium sulfide, phosphorus sulfide and a halogen compound.
[0017] Preferably, in step S1, the inert atmosphere is nitrogen or argon with a purity greater than 99.99%, an oxygen content ≤0.01ppm, and a water content ≤0.01ppm; the mixing method is mechanical mixing, rotary mixing, and stirring mixing, the rotation speed is 500-900r / min, and the grinding time is 3-30h.
[0018] Preferably, in step S2, the heat treatment is performed by heating the temperature to 350-650°C and keeping the temperature for 2-48 hours, and the heating rate is 1-10°C / min.
[0019] Preferably, in step S3, the cooling rate is 1-1000°C / min.
[0020] And a solid electrolyte material with high ionic conductivity for a solid-state battery, which is prepared by the above-mentioned method for preparing the solid electrolyte material with high ionic conductivity for a solid-state battery.
[0021] Compared with the prior art, the advantages of the present invention are:
[0022] 1. The preparation of pure-phase sulfide solid electrolytes in a solvent-free, dry process can reduce the generation of impurities, thereby improving the purity and ionic conductivity of the sulfide solid electrolyte and enhancing the electrochemical stability. At the same time, high-purity sulfide solid electrolytes can help further improve the rate performance and energy density of all-solid-state batteries, providing a solid material foundation for the performance improvement and reliability of all-solid-state batteries;
[0023] 2. By introducing solid purifiers and / or gas purifiers, impurities such as Li2S, LiCl, LiBr, LiI, etc., including but not limited to the above impurities, can be effectively removed, thereby improving the purity of the sulfide solid electrolyte;
[0024] 3. Through this dry purification process, a sulfide solid electrolyte with high purity can be simply and effectively prepared. The method is simple and the product quality is controllable, which is conducive to the commercial application of sulfide solid electrolytes in all-solid-state batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Schematic diagram of the preparation process of Example A in the present invention;
[0026] Figure 2 Schematic diagram of the preparation process of Example B of the present invention;
[0027] Figure 3 Schematic diagram of the preparation process of Example C of the present invention;
[0028] Figure 4 XRD patterns of the sulfide solid electrolytes prepared in Examples 1, 2, 3 and Comparative Examples 1, 3, 4;
[0029] Figure 5 The XRD spectra of the sulfide solid electrolytes prepared in Example 4 and Comparative Example 2 are shown. DETAILED DESCRIPTION
[0030] The present invention is further described in detail below with reference to the accompanying drawings.
[0031] Embodiment A,
[0032] A method for preparing a solid electrolyte material with high ionic conductivity for a solid-state battery comprises the following steps:
[0033] S1. Under the protection of an inert atmosphere, the mixed raw material and the solid purifying agent are mixed to obtain a powder after uniform mixing;
[0034] S2, heat treating the powder;
[0035] S3. After cooling, a sulfide solid electrolyte is obtained.
[0036] In step S1, the inert atmosphere is nitrogen or argon with a purity greater than 99.99%, an oxygen content ≤ 0.01 ppm, and a water content ≤ 0.01 ppm.
[0037] In step S1, the mixed raw material includes lithium sulfide and phosphorus sulfide; or, the mixed raw material includes lithium sulfide, phosphorus sulfide and a halogen compound.
[0038] In step S1, the solid purifying agent is a pure sulfur element or a mixture whose main phase is sulfur element or one or a combination of at least two of sublimated sulfur, amorphous sulfur, refined sulfur, P2S5, P4S3, and the content of the solid purifying agent is 0.5-1.5wt%.
[0039] In step S1, the mixing method is mechanical mixing, rotary mixing, stirring mixing, the rotation speed is 500-900 r / min, and the grinding time is 3-30 hours.
[0040] In step S2, the heat treatment is to increase the temperature to 350-650°C and keep the temperature for 2-48 hours, and the heating rate is 1-10°C / min.
[0041] In step S3, the cooling rate is 1 to 1000°C / min.
[0042] Embodiment B,
[0043] A method for preparing a solid electrolyte material with high ionic conductivity for a solid-state battery comprises the following steps:
[0044] S1. Under the protection of an inert atmosphere, the mixed raw materials are mixed to obtain a powder after uniform mixing;
[0045] S2, introducing a gas purifying agent and heat treating the powder;
[0046] S3. After cooling, a sulfide solid electrolyte is obtained.
[0047] In step S1, the inert atmosphere is nitrogen or argon with a purity greater than 99.99%, an oxygen content ≤ 0.01 ppm, and a water content ≤ 0.01 ppm.
[0048] In step S1, the mixed raw material includes lithium sulfide and phosphorus sulfide; or, the mixed raw material includes lithium sulfide, phosphorus sulfide and a halogen compound.
[0049] In step S1, the mixing method is mechanical mixing, rotary mixing, stirring mixing, the rotation speed is 500-900 r / min, and the grinding time is 3-30 hours.
[0050] In step S2, the gas purifying agent is one of H2S and S2 or a combination of the two, and the flow rate of the gas purifying agent is 0.5-3 mL / s.
[0051] In step S2, the heat treatment is to increase the temperature to 350-650°C and keep the temperature for 2-48 hours, and the heating rate is 1-10°C / min.
[0052] In step S3, the cooling rate is 1 to 1000°C / min.
[0053] Example C
[0054] A method for preparing a solid electrolyte material with high ionic conductivity for a solid-state battery comprises the following steps:
[0055] S1. Under the protection of an inert atmosphere, the mixed raw material and the solid purifying agent are mixed to obtain a powder after uniform mixing;
[0056] S2, introducing a gas purifying agent and heat treating the powder;
[0057] S3. After cooling, a sulfide solid electrolyte is obtained.
[0058] In step S1, the inert atmosphere is nitrogen or argon with a purity greater than 99.99%, an oxygen content ≤ 0.01 ppm, and a water content ≤ 0.01 ppm.
[0059] In step S1, the mixed raw material includes lithium sulfide and phosphorus sulfide; or, the mixed raw material includes lithium sulfide, phosphorus sulfide and a halogen compound.
[0060] In step S1, the solid purifying agent is a pure sulfur element or a mixture whose main phase is sulfur element or one or a combination of at least two of sublimated sulfur, amorphous sulfur, refined sulfur, P2S5, P4S3, and the content of the solid purifying agent is 0.5-1.5wt%.
[0061] In step S1, the mixing method is mechanical mixing, rotary mixing, stirring mixing, the rotation speed is 500-900 r / min, and the grinding time is 3-30 hours.
[0062] In step S2, the gas purifying agent is one of H2S and S2 or a combination of the two, and the flow rate of the gas purifying agent is 0.5-3 mL / s.
[0063] In step S2, the heat treatment is to increase the temperature to 350-650°C and keep the temperature for 2-48 hours, and the heating rate is 1-10°C / min.
[0064] In step S3, the cooling rate is 1 to 1000°C / min.
[0065] Embodiment 1,
[0066] A method for preparing a solid electrolyte material with high ionic conductivity for a solid-state battery comprises the following steps:
[0067] S1. Under the protection of nitrogen atmosphere (O2≤0.01ppm, H2O≤0.01ppm), 4.28gLi2S, 4.141gP2S5, 1.579gLiCl and 0.12g (1.2wt%) elemental sulfur were fully ground and mixed at a grinding speed of 500r / min for 8h to obtain powder after uniform mixing;
[0068] S2, heat-treating the powder, heating it to 500°C at a heating rate of 2°C / min and keeping it at that temperature for 16 hours;
[0069] S3. Cool to room temperature at a cooling rate of 2°C / min to obtain Li6PS5Cl solid electrolyte.
[0070] Embodiment 2,
[0071] A method for preparing a solid electrolyte material with high ionic conductivity for a solid-state battery comprises the following steps:
[0072] S1. Under the protection of nitrogen atmosphere (O2≤0.01ppm, H2O≤0.01ppm), 4.28gLi2S, 4.141gP2S5 and 1.579gLiCl were fully ground and mixed at a grinding speed of 500r / min for 8h to obtain powder after uniform mixing;
[0073] S2, introduce H2S gas with a flow rate of 1 mL / s, and heat treat the powder by heating it to 500°C at a heating rate of 2°C / min and keeping it at that temperature for 16 h;
[0074] S3. Cool to room temperature at a cooling rate of 2°C / min to obtain Li6PS5Cl solid electrolyte.
[0075] Embodiment 3,
[0076] A method for preparing a solid electrolyte material with high ionic conductivity for a solid-state battery comprises the following steps:
[0077] S1. Under the protection of nitrogen atmosphere (O2≤0.01ppm, H2O≤0.01ppm), 4.28gLi2S, 4.141gP2S5, 1.579gLiCl and 0.12g (1.2wt%) elemental sulfur were fully ground and mixed at a grinding speed of 500r / min for 8h to obtain powder after uniform mixing;
[0078] S2, introduce H2S gas with a flow rate of 1 mL / s, and heat treat the powder by heating it to 500°C at a heating rate of 2°C / min and keeping it at that temperature for 16 h;
[0079] S3. Cool to room temperature at a cooling rate of 2°C / min to obtain Li6PS5Cl solid electrolyte.
[0080] Embodiment 4,
[0081] A method for preparing a solid electrolyte material with high ionic conductivity for a solid-state battery comprises the following steps:
[0082] S1. Under the protection of nitrogen atmosphere (O2≤0.01ppm, H2O≤0.01ppm), 3.902gLi2S, 3.775gP2S5, 2.323gGeS2 and 0.12g (1.2wt%) elemental sulfur were fully ground and mixed at a grinding speed of 500r / min for 8h to obtain powder after uniform mixing;
[0083] S2, introduce H2S gas with a flow rate of 1 mL / s, and heat treat the powder by heating it to 600°C at a heating rate of 2°C / min and keeping it at that temperature for 4 h;
[0084] S3, cooled to room temperature at a cooling rate of 2 ° C / min to obtain Li 10 GeP2S 12 Solid electrolyte.
[0085] Comparative Example 1
[0086] A method for preparing a sulfide solid electrolyte comprises the following steps:
[0087] S1. Under the protection of nitrogen atmosphere (O2≤0.01ppm, H2O≤0.01ppm), 4.28gLi2S, 4.141gP2S5 and 1.579gLiCl were fully ground and mixed at a grinding speed of 500r / min for 8h to obtain powder after uniform mixing;
[0088] S2, introducing N2 gas with a flow rate of 1 mL / s, and heat treating the powder by heating it to 500°C at a heating rate of 2°C / min and keeping it at that temperature for 16 h;
[0089] S3. Cool to room temperature at a cooling rate of 2°C / min to obtain Li6PS5Cl solid electrolyte.
[0090] Comparative Example 2
[0091] A method for preparing a sulfide solid electrolyte comprises the following steps:
[0092] S1. Under the protection of nitrogen atmosphere (O2≤0.01ppm, H2O≤0.01ppm), 3.902gLi2S, 3.775gP2S5 and 2.323gGeS2 were fully ground and mixed at a grinding speed of 500r / min for 8h to obtain powder after uniform mixing;
[0093] S2, introducing N2 gas with a flow rate of 1 mL / s, and heat treating the powder by heating it to 600°C at a heating rate of 2°C / min and keeping it at that temperature for 4 h;
[0094] S3, cooled to room temperature at a cooling rate of 2 ° C / min to obtain Li 10 GeP2S 12 Solid electrolyte.
[0095] Comparative Example 3
[0096] A method for preparing a sulfide solid electrolyte comprises the following steps:
[0097] S1. Under the protection of nitrogen atmosphere (O2≤0.01ppm, H2O≤0.01ppm), 4.28gLi2S, 4.141gP2S5, 1.579gLiCl and 0.03g (0.3wt%) elemental sulfur were fully ground and mixed at a grinding speed of 500r / min for 8h to obtain powder after uniform mixing;
[0098] S2, heat-treating the powder, heating it to 500°C at a heating rate of 2°C / min and keeping it at that temperature for 16 hours;
[0099] S3. Cool to room temperature at a cooling rate of 2°C / min to obtain Li6PS5Cl solid electrolyte.
[0100] Comparative Example 4
[0101] A method for preparing a sulfide solid electrolyte comprises the following steps:
[0102] S1. Under the protection of nitrogen atmosphere (O2≤0.01ppm, H2O≤0.01ppm), 4.28gLi2S, 4.141gP2S5, 1.579gLiCl and 0.18g (1.8wt%) elemental sulfur were fully ground and mixed at a grinding speed of 500r / min for 8h to obtain powder after uniform mixing;
[0103] S2, heat-treating the powder, heating it to 500°C at a heating rate of 2°C / min and keeping it at that temperature for 16 hours;
[0104] S3. Cool to room temperature at a cooling rate of 2°C / min to obtain Li6PS5Cl solid electrolyte.
[0105] The solid electrolytes obtained in Examples 1-4 and Comparative Examples 1-4 were ground respectively, and their XRD spectra (such as Figure 4 and Figure 5 The XRD spectrum is used to confirm whether there is an impurity phase, and the EIS curve is used to confirm the ionic conductivity. The results are shown in the following table:
[0106]
[0107] According to the test results of Examples 1-4 and Comparative Examples 1-2, by introducing a solid purifier and / or a gas purifier, impurities such as Li2S, LiCl, LiBr, and LiI, including but not limited to the above impurities, can be effectively removed, thereby improving the purity and ionic conductivity of the sulfide solid electrolyte, and the ionic conductivity is increased by about 35 to 64%.
[0108] According to the test results of Example 1 and Comparative Examples 3 and 4, it can be seen that the introduction of too much or too little solid purifying agent fails to effectively eliminate the impurity phase. When the introduction of too little purifying agent, the too little purifying agent fails to completely replace the original oxygen element in the powder. Secondly, during the heat treatment process, the sulfur element is not fully replenished with the volatilization of P2S5, and the impurity phase cannot be effectively eliminated. When too much purifying agent is introduced, the stoichiometric ratio of the mixed raw materials will be unbalanced, and a second phase (impurity phase) will be generated. It can be seen that the introduction of too much or too little solid purifying agent fails to achieve the purpose of purification.
[0109] It should be noted that the sulfide solid electrolyte prepared above can be a glass ceramic obtained by heating the sulfide solid electrolyte to above the crystallization temperature, or can be a sulfide having a crystal structure, such as Li3PS4 crystal structure, Li4P2S6 crystal structure, Li7PS6 crystal structure, Li7P3S 11 Crystal structure, Li 12 GeP2S 10 Crystal structure.
[0110] The present invention is described above by way of example in conjunction with the accompanying drawings. It is obvious that the implementation of the present invention is not limited to the above-mentioned method. As long as various improvements are made using the method concept and technical solution of the present invention, or the concept and technical solution of the present invention are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.
Claims
1. A method for preparing a solid electrolyte material with high ionic conductivity for a solid-state battery, characterized in that: The following steps are involved: S1. Under the protection of an inert atmosphere, the mixed raw material and the solid purifying agent are mixed to obtain a powder after uniform mixing; S2, heat treating the powder; S3. After cooling, a sulfide solid electrolyte is obtained.
2. The method for preparing a solid electrolyte material with high ionic conductivity for a solid-state battery according to claim 1, characterized in that: In step S1, the solid purifying agent is a pure sulfur element or a mixture whose main phase is sulfur element or one or a combination of at least two of sublimated sulfur, amorphous sulfur, refined sulfur, P2S5, P4S3, and the content of the solid purifying agent is 0.5-1.5wt%.
3. The method for preparing a solid electrolyte material with high ionic conductivity for a solid-state battery according to claim 1, characterized in that: In the step S2, a gas purifying agent is introduced while the powder is being heat treated.
4. A method for preparing a solid electrolyte material with high ionic conductivity for a solid-state battery, characterized in that The following steps are involved: S1. Under the protection of an inert atmosphere, the mixed raw materials are mixed to obtain a powder after uniform mixing; S2, introducing a gas purifying agent and heat treating the powder; S3. After cooling, a sulfide solid electrolyte is obtained.
5. A method for preparing a solid electrolyte material with high ionic conductivity for a solid-state battery according to claim 3 or 4, characterized in that: In the step S2, the gas purifying agent is one of H2S and S2 or a combination of the two, and the flow rate of the gas purifying agent is 0.5-3 mL / s.
6. A method for preparing a solid electrolyte material with high ionic conductivity for a solid-state battery according to claim 1 or 4, characterized in that: In the step S1, the mixed raw material includes lithium sulfide and phosphorus sulfide; Alternatively, the mixed raw material includes lithium sulfide, phosphorus sulfide and a halogen compound.
7. A method for preparing a solid electrolyte material with high ionic conductivity for a solid-state battery according to claim 1 or 4, characterized in that: In step S1, the inert atmosphere is nitrogen or argon with a purity greater than 99.99%, an oxygen content of ≤0.01ppm, and a water content of ≤0.01ppm; the mixing method is mechanical mixing, rotary mixing, and stirring mixing, the rotation speed is 500-900r / min, and the grinding time is 3-30h.
8. The method for preparing a solid electrolyte material with high ionic conductivity for a solid-state battery according to claim 1 or 4, characterized in that: In step S2, the heat treatment is to increase the temperature to 350-650°C and keep the temperature for 2-48 hours, and the heating rate is 1-10°C / min.
9. The method for preparing a solid electrolyte material with high ionic conductivity for a solid-state battery according to claim 1 or 4, characterized in that: In the step S3, the cooling rate is 1-1000°C / min.
10. A solid electrolyte material with high ionic conductivity for a solid-state battery, characterized in that: The solid electrolyte material with high ionic conductivity for solid-state batteries is prepared by the method for preparing the solid electrolyte material with high ionic conductivity as claimed in any one of claims 1 to 9.